Understanding Early Marriages in Timor-Leste's Rural Borders Contexts: A Human Rights Approach - DULCE, Martin (Universitas Airlangga, 2026)
Early marriage remains a significant issue in rural border areas of Timor-Leste, where socio-economic pressures and cultural norms often undermine the rights and development of young girls. This study aims to investigate the factors contributing to early marriage, the community's perception of its human rights implication, and the role of entrenched social norms in perpetuating gender inequality. Using a qualitative case study design semi-structured interviews and focus group discussions were conducted with young girls, their families, community leaders, and local authorities in selected rural villages. The findings reveal that economic necessity and cultural traditions drive early marriage, with families viewing it as a means of securing financial stability and social acceptance. Community perception indicates a gap between awareness of human rights and the prevailing cultural practices that endorse early marriage. The study underscores the urgency of enhancing educational access and economic opportunities for girls, engaging community members in dialogue about gender norms, and advocating for policies that protect children’s rights. This insight can inform targeted interventions aimed at reducing early marriage rates and empowering young women in Timor-Leste, ultimately contributing to broader goals of gender equality and human rights.